Philippines : Development Policy Update - World Bank (Washington, DC, 2013)
The Philippines has achieved reasonable economic growth of about 4 percent per annum over the past two years, in spite of adverse global developments, sporadic conflict in Mindanao, political uncertainty and investor concerns regarding fiscal sustainability. The economy has been particularly resilient in view of concerns regarding fiscal management and the limited recovery in investment since the 1997 Asian financial crisis. The persistent low levels of investment - below 20 percent of GNP compared with about 23 percent in the early to mid 1990s - raises concerns about future growth. In recent years it has been consumption rather than investment that has underpinned growth, and this cannot continue indefinitely. Sustained geographically dispersed economic growth and relatively stable prices have resulted in a decline in poverty. Both the public and private sector will need to contribute for the Philippines to more fully achieve its development objectives. Three issues are central to improved public sector performance - fiscal management, off-budget losses and contingent liabilities, and governance. Mindful of the Philippines' relatively poor competitiveness and that growth, employment creation and poverty reduction depend critically on private sector performance, this update focuses on three key investment issues - infrastructure, the financial sector, and competition.